Effects of gold nanoparticles in gilthead seabream—A proteomic approach - Barreto, A. (2021)
Despite the widespread use of nanoparticles (NPs), there are still major gaps of knowledge regarding the impact of nanomaterials in the environment and aquatic animals. The present work aimed to study the effects of 7 and 40 nm gold nanoparticles (AuNPs) – citrate and polyvinylpyrrolidone (PVP) coated – on the liver proteome of the estuarine/marine fish gilthead seabream (Sparus aurata). After 96 h, exposure to AuNP elicited alterations on the abundance of 26 proteins, when compared to the control group.